Critical factors that affect the functioning of a research and evaluation capacity building partnership: A causal loop diagram - Tobin, Rochelle; Crawford, Gemma; Hallett, Jonathan; Maycock, Bruce; Lobo, Roanna (2022)
Introduction: Public health policy and practice is strengthened by the application of quality evidence to decision making. However, there is limited understanding of how initiatives that support the generation and use of evidence in public health are operationalised. This study examines factors that support the internal functioning of a partnership, the Western Australian Sexual Health and Blood-borne Virus Applied Research and Evaluation Network (SiREN). SiREN aims to build research and evaluation capacity and increase evidence-informed decision making in a public health context.